Sistem Pemesanan Jasa Arsitek Berbasis Web Pada Arunika Loya Design - Niken Rakhmayanti; Sinta Tridian Galih; Cristeddy Asa Bakti (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Service management in creative fields such as architectural services needs to be done with a neat and efficient system. Currently, Arunika Loya Design still uses a manual way of receiving orders, which often makes it difficult to manage data and communicate with clients. This research aims to design a web-based architectural service booking system using the Waterfall model. Data is obtained through observation, interviews, and literature studies. This system facilitates online ordering, client and project data management, and communication via the WhatsApp button. The design was made with Figma, and the system was built using Laravel, HTML, CSS, and MySQL. Black Box testing was used to show that all features work. As a result, this system increases efficiency, clarifies project management, and facilitates interaction between clients and admins.